2020
DOI: 10.1016/j.tem.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and Metabolic Insights from Pancreatic Surgery

Abstract: Although it is well established that diabetes can also develop as a result of diseases or maneuvers on the exocrine pancreas, the complex relationship between glucose disorders and underlying pancreatic disease is still debated. There is evidence that several features linked to pancreatic diseases can modify endocrine and metabolic conditions before and after surgery. However, pancreatic surgery provides a rare opportunity to correlate in vivo endocrine and metabolic pathways with ex vivo pancreatic samples, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 103 publications
3
17
0
Order By: Relevance
“…Several studies have examined the metabolic changes occurring following partial pancreatectomy in humans (14,15) and have suggested that the acute removal of beta-cell mass inevitably accelerates a decline in betacell functional capacity, already "stressed" by the attempt to compensate for increasing insulin demand. (7,16) In the present study we aim to evaluate: (1) the changes in beta-cell secretory capacity, modelled from an oral glucose tolerance test (OGTT) and hyperglycemic clamp (HC) in non-diabetic individuals before and after acute beta-cell reduction and (2) whether pre-existing insulin secretory defects can predict glucose disarrangements following a reduction in beta-cell mass.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the metabolic changes occurring following partial pancreatectomy in humans (14,15) and have suggested that the acute removal of beta-cell mass inevitably accelerates a decline in betacell functional capacity, already "stressed" by the attempt to compensate for increasing insulin demand. (7,16) In the present study we aim to evaluate: (1) the changes in beta-cell secretory capacity, modelled from an oral glucose tolerance test (OGTT) and hyperglycemic clamp (HC) in non-diabetic individuals before and after acute beta-cell reduction and (2) whether pre-existing insulin secretory defects can predict glucose disarrangements following a reduction in beta-cell mass.…”
Section: Introductionmentioning
confidence: 99%
“…Human islets have been previously described as sparsely innervated and the potential role of noradrenergic fibers in diabetes onset has been ascribed to the regulation of blood flow within the islet [17].Using electron microscopy we were instead able to observe that these fibers were in direct contact with endocrine cells bearing typical insulin granules and morphology [40,41], thus bona fide beta-cells, suggesting a direct interplay between innervation and beta-cells. Using the extraordinary advantage of the pancreatic surgery group and in vivo insulin secretion study [42], we linked innervation to beta-cell function and glucose tolerance. We verified whether noradrenergic fibers were related to altered insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…All experiments were performed on freshly isolated pancreas samples from living patients undergoing partial pancreatectomy. These are extremely valuable tissues, and we believe that pancreatic surgery provides a rare opportunity to correlate in vivo endocrine and metabolic pathways (before surgery) with ex vivo data generated after collecting the pancreatic samples [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…All experiments were performed on freshly isolated pancreas samples from living patients undergoing partial pancreatectomy. These are extremely valuable tissues, and we believe that pancreatic surgery provides a rare opportunity to correlate in vivo endocrine and metabolic pathways (before surgery) with ex vivo data generated after collecting the pancreatic samples [16] Previous reports on cell culture and peripheral blood mononuclear cells (PBMCs) have reported that silica gel column technology using the RNeasy Mini-/Microkit is superior in its ability to extract high-quality RNA compared to protocols using the traditional guanidine isothiocyanate extraction method [17], which is mostly explained by the high binding power of silica gel columns. There also appears to be a different outcome in terms of RNA quantity and quality between the two methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation